Chilean perpetrators in Chili-impressions: repression from a transnational perspective - Amaral de Aguiar, Carolina (Revista de Historia Social y de las Mentalidades, 2023)
This research dialogues with recent studies on the figure of the perpetrator to analyze how the agents of Chilean repression are represented in the audiovisual media. From methodologies from studies on the relationship between audiovisual and history, this article analyzes the narrative mechanisms used by the French public television documentary series Chili-impressions (1978), directed by the Spanish exile José María Berzosa, to construct an opposition to the Chilean military junta in the seventies. The audiovisual product studied is emblematic of having achieved great visibility at the time after its screening was initially suspended by the French justice system and for collaborating with the dissemination of a negative memory of the dictatorship abroad.
Keywords: Television Series; Dictatorship; Documentary; Perpetrators